Dysregulation of metallothionein and circadian genes in human hepatocellular carcinoma. (7th February 2017) - Li, Huan; Lu, Yuan-Fu; Chen, Hong; Liu, Jie
ABSTRACT: Hepatocellular carcinoma (HCC) is the major threat to human health, and disruption of circadian clock genes is implicated in hepatocarcinogenesis. This study examined the dysregulation of metallothioneins and circadian genes in achieved human HCC ( n = 24), peri-HCC tissues ( n = 24) as compared with normal human livers ( n = 36). Total RNA was extracted and reverse transcribed. Real-time RT-qPCR was performed to determine the expression of genes of interest. The results demonstrated the downregulation of metallothionein-1 (MT-1), MT-2, and metal transcription factor-1 (MFT-1) in human HCC as compared with Peri-HCC and normal tissues. MTs are a biomarker for HCC and have typical circadian rhythms; the expression of major circadian clock genes was also determined. HCC produced a dramatic decrease in the expression of core clock genes, circadian locomotor output cycles kaput (Clock) and brain and muscle Arnt-like protein 1 (Bmal1), and decreased the expression of the clock feedback control genes, Periods (Per1, Per2) and Cryptochromes (Cry1, Cry2). On the other hand, the expression of clock target genes nuclear orphan receptor factor protein (Nr1d1) and D-box-binding protein (Dbp) was upregulated as compared with Peri-HCC and normal livers. Peri-HCC also had mild alterations in these gene expressions. In summary, the present study clearly demonstrated the dysregulation of MTs and circadian clock genes in human HCC, which could provide the information of targeting MT and circadian clock in HCC management.